2019
DOI: 10.1016/j.stemcr.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Motor Neuron Resilience in ALS Using Stem Cells

Abstract: Summary Oculomotor neurons, which regulate eye movement, are resilient to degeneration in the lethal motor neuron disease amyotrophic lateral sclerosis (ALS). It would be highly advantageous if motor neuron resilience could be modeled in vitro . Toward this goal, we generated a high proportion of oculomotor neurons from mouse embryonic stem cells through temporal overexpression of PHOX2A in neuronal progenitors. We demonstrate, using electrophysiology, immunocytochemistry, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…ALS and SMA are characterized by a selective loss of motor neurons, but OMNs that control extraocular muscles (EOMs) are resistant to degeneration in these fatal diseases [11,24,29,32,55]. Even stem cell-derived OMNs show an increased resilience to ALS-like toxicity compared to in vitro derived spinal motor neurons [3]. Identification of the cell intrinsic mechanisms responsible for this differential vulnerability could allow the development of therapies to prevent or slow down the progressive motor neuron loss.…”
Section: Discussionmentioning
confidence: 99%
“…ALS and SMA are characterized by a selective loss of motor neurons, but OMNs that control extraocular muscles (EOMs) are resistant to degeneration in these fatal diseases [11,24,29,32,55]. Even stem cell-derived OMNs show an increased resilience to ALS-like toxicity compared to in vitro derived spinal motor neurons [3]. Identification of the cell intrinsic mechanisms responsible for this differential vulnerability could allow the development of therapies to prevent or slow down the progressive motor neuron loss.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Nrp1 and Dbn1 are involved in axonal function, and Nek1 is a known ALS-causative gene (Brenner et al, 2016;Kenna et al, 2016;Nijssen et al, 2018). Axon-seq is an advanced technique for sequencing the RNA in axons, and thus can provide enhanced knowledge about peripheral nerve biology to explain the vulnerability/resilience of MN (Nijssen et al, 2017;Allodi et al, 2019) and to identify the treatment of MN diseases.…”
Section: Lessons From Different Nervous Systemsmentioning
confidence: 99%
“…Indeed, given the peculiar characteristics of Onuf's and oculomotor MNs described above (up/down regulation of specific genes compared to spinal MNs as showed in Kaplan et al, 2014;Allodi et al, 2019), it is not surprising that these neurons respond differently in ALS compared to the other MNs, remaining resistant to degeneration until the later stages of the disease. For instance, as stated, it has been demonstrated that MMP9 is highly expressed by ALS-affected spinal MNs, whereas its expression is absent in Onuf's neurons; on the contrary, the protein OPN is selectively expressed by ALS-resistant pool, while downregulated in vulnerable MNs (Kaplan et al, 2014).…”
Section: Amyotrophic Lateral Sclerosis and Spinal Muscular Atrophymentioning
confidence: 99%
“…The differential vulnerability of Onuf's neurons has been initially attributed to their cytoarchitecture, connectivity, and metabolic rate (Onuf, 1899;Schrøder, 1981;Gibson et al, 1988;Shaw and Eggett, 2000). Only recently, in the XXI century, it has been evaluated by more sophisticated genetic and molecular analyses (Kaplan et al, 2014;Allodi et al, 2019).…”
Section: Recent Insights From Genomics and Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation